Involvement of IL-10 in exhaustion of myeloid dendritic cells and rescue by CD40 stimulation - Kajino, Kiichi (Blackwell Publishing Inc, 2007)
It has recently been shown that immature dendritic cells (DCs) stimulated by a danger signal undergo transient maturation followed by exhaustion. However, the exact mechanism for this has not been elucidated. In this study, we show that interleukin-10 (IL-10) secreted from transiently matured DCs stimulated by danger signals is responsible for this rapid DC exhaustion. Blocking of the autocrine IL-10 enabled transient mature DCs to maintain the mature phenotype for several days. However, these DCs remained phenotypically unstable because the addition of IL-10 altered the transient mature DCs to exhausted DCs. More importantly, stimulation of DCs by CD40 protected transient mature DCs from IL-10-dependent exhaustion, with the result that mature DCs remained stable in the presence of IL-10. Furthermore, in vivo administration of stable mature DCs pulsed with ovalbumin protein induced antigen-specific cytotoxic T lymphocytes (CTLs) effectively, whereas neither exhausted DCs nor transient mature DCs were able to prime a strong antigen-specific CTL response. These results indicate that DC−T cell engagement via CD40−CD154 is required for stable DC maturation leading to effective CTL induction. Otherwise, DCs stimulated solely by a danger signal are temporarily activated, but then rapidly lose their immune-activating capacity under the influence of autocrine IL-10.